THE CORRELATION BETWEEN STUDENTS’ PERSONALITY TRAITS AND THEIR WRITING ABILITY - s sucianik; harum natasha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The purpose of learning English is to develop the students competence in oral and written communication in order to reach the functional literacy. State Senior High School 2 Rambah Hilir 2 Rokan Hulu Regency is one of the schools that used this curriculum learning process. After doing the observation at school, the problems identified are: some of the students are good at writing, but not good at speaking; some others are not good at writing, but excellent at speaking. This research was aimed at determining whether there is a significant correlation between students’ personality traits and their writing ability. This research was a correlational research. The instruments of the research were psychological test that was adopted from Big Five Inventory and test of writing ability. In analyzing the data, the writer used Pearson product moment correlation coefficient. The result of the research was detailed based on its five indicators, as follow: extraversion = 0.839, agreeableness = 0.849, conscientiousness = 0.703, neuroticism = -0.114, and openness = 0.825, higher than r table at level 5% (0.413) and 1% (0.526). In short, Null hypothesis (Ho) is rejected. It can be concluded that students’ personality traits are strongly correlated with their writing ability at State Senior High School 2 Rambah Hilir Rokan Hulu Regency.